Saberes e fazeres docentes em arte visual na educação infantil - Veronesi, Valquiria Bertuzzi (2017)
A qualitative nature conducted research focused on the knowledge and practices related to Visual Art of a group of Early Childhood Education teachers. As general purpose attempts to identify the knowledge and practices of those teachers proposal for small children in Art. As specific purposes, to analyze possibilities in Visual Art knowledge construction in permanent and inservice teachers training and to understand how the knowledge built in this space unfolds in the practices with children from 4 -5 years of age. Carried out with 7 teachers and the Pedagogical Assistant (AP) the research took place in a Municipal Early Childhood Education and Elementary School (EMEIEF), in Santo André, named by us: EMEIEF Kaleidoscope. A data collection, as methodological procedure, from characterization forms; questionnaires; formative meetings; recorded and transcribed meetings; photographic records of teachers and children production; reading and analysis of the Pedagogical Political Project and plannings. The Content Analysis proposed by Bardin (2016) was used to analyze the data. The theoretical reference was organized as follows: for the historical rescue of the Teaching of Art in Brazil and its foundations we hold ourselves in Ana Mae Barbosa (2002, 2008, 2012) and other scholars of the History of Education. In relation to Art in the interface with the culture of childhood we count on Ana Lúcia Goulart de Faria (2002, 2013, 2015) and the Brazilian legislation; Vygotsky (1998, 1999, 2001) brings contributions to the understanding of children's development and Art; Paulo Freire (1982, 1987, 1992, 1996, 1997, 2001, 2005) and Tardif (2002, 2006) refer us to important reflections on the conscience of the teacher profession, viewing to highlight essential basis of teaching, training and its challenges. As a result we find that the practices and discourses of teachers are reflections of their personal and professional paths. The consciousness of the fragility in their formations is signaled by them, especially when they demand permanent formation.